Lurbinectedin in the treatment of relapsed small cell lung cancer - Baena, Javier; Modrego, Andrea; Zeaiter, Ali; Kahatt, Carmen; Alfaro, Vicente; Jimenez-Aguilar, Elizabeth; Mazarico, Jose María; Paz-Ares, Luis (Future oncology (London, England), 2021)
Lurbinectedin is a marine-derived drug that inhibits transcription, a process that is frequently dysregulated in small cell lung cancer. The activity of lurbinectedin has been studied in many solid tumors, showing not only promising results but also a favorable safety profile. In relapsed small cell lung cancer, the drug has shown encouraging activity both as a single agent and in combination with doxorubicin, paclitaxel or irinotecan. The USA FDA has recently granted accelerated approval to lurbinectedin monotherapy in this setting. This article provides an update on available data and ongoing studies of lurbinectedin in small cell lung cancer, including Phase I combination trials, the basket Phase II trial and the ATLANTIS Phase III trial. Lung cancer is currently responsible for a large number of cancer deaths worldwide. Small cell lung cancer (SCLC) is considered the most aggressive subtype of lung cancer. When a patient presents with extensive SCLC, first-line treatment needs to be used. The most appropriate treatment option for the patient is selected; however, it is possible for the cancer to continue to get worse, even over a brief period of time. The patient will then be given another treatment; however, studies on the effectiveness of classical second-line drugs are scarce. For this reason, new therapies for SCLC are in development. One of these treatments is a marine-derived drug called lurbinectedin, which shows promising activity in some solid tumors, such as extensive SCLC, after failure of first-line treatment. Here the authors present the results of the main trials related to the activity of lurbinectedin either alone or in combination with other drugs for this type of cancer.